Developing a sample doodle book introducing Filipino artists through the elements and principles of art for the grade 12 art attack - Abad, Ma. Stephanie Pearl E.; Cruz, May Lyn (Quezon City College of Fine Arts, University of the Philippines Diliman, 2017)
The main purpose of this thesis is to introduce Filipino artists through the elements and principles of art in grade 12 specialization subject: integrating the elements and principles of organization in the arts. This will be executed by creating an educational resource for this subject through the means of a sample doodle activity book. The first chapter of this thesis reveals the background of the thesis goals and the related literature written about these topics. The theories of John Dewey and Alexis Clements on art as experience is discussed. Further sources on teaching secondary art and the effectiveness of doodling are also introduced. The second chapter focuses on the development of the K-12 curriculum and how it compares to the K-10 curriculum. Further discussion on the senior high school art track also reveals its components and the proposed curriculum. Chapter three gives a short history on Philippine modern art and the five artists that are in focus in the sample doodle activity chapters. A short biography is given to each and formal analysis on their works conclude why they were chosen to be featured in the doodle chapters. The fourth chapter narrates the steps on how the doodle chapters were made and developed. Book inspirations were the main foundation of the chapters. The last chapter concludes how the theories and related literature in this thesis supports the effectiveness of using the doodle chapters in the art track curriculum.
Thesis (Bachelor of Fine Arts (Art Education))--University of the Philippines Diliman
Bibliography: leaves 86-93.
Keywords: Doodling; Doodles; Artists -- Philippines -- Biography